Good teaching and learning : pupils and teachers speak - Morgan, Colin; Morris, Glyn. (Buckingham : Open University Press, 1999)
This book is about: Pupils and learning; Pupils and teachers; Pupils and lessons; Teachers and pupil learning; ...
Keywords: High school teaching; Evaluation; Case studies; High school teaching -- Great Britain -- Evaluation -- Case studies; Learning -- Evaluation -- Case studies; Teachers -- Self-rating of -- Great Britain -- Case studies; Comprehensive high schools -- Wales -- Case studies